Passive Leg Raise: Feasibility and Safety of the Maneuver in Patients With Undifferentiated Shock. (October 2020) - Toppen, William; Aquije Montoya, Elizabeth; Ong, Stephanie; Markovic, Daniela; Kao, Yuhan; Xu, Xueqing; Chiem, Alan; Cannesson, Maxime; Berlin, David; Barjaktarevic, Igor
Purpose: Passive leg raise (PLR), in combination with technologies capable of capturing stroke volume changes, has been widely adopted in the management of shock. However, dedicated evaluation of safety, feasibility, and receptiveness of patients and nursing staff to PLR maneuver is missing. Methods: A noninterventional, prospective trial recruited adult patients with onset of undifferentiated shock within 24 hours with persistent vasopressor requirements despite fluid resuscitation. A standardized PLR maneuver was used to compare two noninvasive hemodynamic monitoring systems, each without significant impact on the performance of the maneuver. Safety and efficacy of the PLR were evaluated via subjective and objective measures. Objective measures of patient comfort and tolerance were evaluated through changes in vital signs, sedation, and analgesia requirements. Nurses and awake patients completed surveys on their experience. Results: Seventy-nine patients were enrolled. Testing was aborted in 2 cases for medical reasons (one patient developed rapid atrial fibrillation, second had profound desaturation). Of all, 5.4% of patients required additional vasopressor support after completion of the PLR maneuver due to persistent hypotension and 4.1% of patients required additional sedation. Among awake patients (N = 35), 6% reported pain and 29% reported discomfort. A total of 11% of nurses reported minor technical difficulties with the maneuver. Conclusion: Passive leg raise maneuver leads to a few serious but reversible complications in a selected population of hemodynamically unstable patients. Although it provides relevant diagnostic information, it may impact patient care. Treating physician should be aware of infrequent but possible complications and appreciate the impact of the maneuver on patients' comfort and nursing workload.